Pengaruh Kepuasan Kerja Dan Budaya Organisasi Terhadap Kinerja Perusahaan Daerah Air Minum (Pdam) Tirta Dharma Kota Pangkalpinang - M. Tanggung; Nuryati Nuryati (Fakultas Ekonomi Universitas Bangka Belitung, 2015)
Job satisfaction and organizational culture are very importance to increase the performance of the Regional Drinking Water Company (PDAM) Tirta Dharma Pangkalpinang.. Employees, who are satisfied with the works that have been reached, will be improve their performance, so it will have an impact on improving overall of company performance. This research using census method. The variables of the study are job satisfaction (X1), organizational culture (X2), and the performance of PDAM Tirta Dharma Pangkalpinang (Y). The method of data analysis using multiple linier regression with the F test and t test. The results show that job satisfaction variables (X1) and organizational culture (X2) simultaneously has significant effect on the performance of PDAM Tirta Dharma Pangkalpinang. Base on the F test, Fvalue 55,768 > Fcalculation 3,18 with p value is 0,000 < 0,05. In addition, Adjusted R Square value of 0,666 means that the influence of the independent variable; job satisfaction (X1) and organizational culture (X2) towards the dependent variable; the performance of PDAM Tirta Dharma Pangkalpinang (Y) is 66,6 %. Based on the calculation of the t test is known that partially job satisfaction (X1) and organizational culture (X2) has a significant effect on the performance of PDAM Tirta Dharma Pangkalpinang by the job satisfaction variable (X1) tcountn (6,268) > ttable (2,0057) and the value of organizational culture (X2) 2,561 > ttable (2,0057).